PENGEMBANGAN MODEL REVISIT INTENTION PADA GEOWISATA LAVA BANTAL BERBAH SLEMAN - Setiawati, Anandia Ayu; Wisnalmawati, Wisnalmawati; Arif, Nina Fapari (Strata Business Review, 2025)
This study aims to develop a revisit intention model in the context of geotourism at Lava Bantal Berbah Sleman by examining the direct influence of destination image on revisit intention, as well as the mediating role of tourist satisfaction. The research involved 101 respondents selected using an accidental sampling technique by distributing questionnaires to visitors reachable through WhatsApp groups. The variables measured included destination image, tourist satisfaction, and revisit intention, and the data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (SmartPLS) approach. The findings reveal that destination image has a significant direct effect on revisit intention and that this relationship is strengthened through the mediation of tourist satisfaction. The novelty of this study lies in demonstrating that tourist satisfaction plays a crucial role in enhancing revisit intention within the geotourism context. Practically, these findings contribute to consumer behavior research and offer valuable insights for geotourism managers at Lava Bantal, particularly in optimizing destination image and satisfaction strategies to encourage repeat visitation.